PacBio Single-Molecule Long-Read Sequencing Provides New Light on the Complexity of Full-Length Transcripts in Cattle - Chang, Tianpeng; An, Bingxing; Liang, Mang; Duan, Xinghai; Du, Lili; Cai, Wentao; Zhu, Bo; Gao, Xue; Chen, Yan; Xu, Lingyang; Zhang, Lupei; Gao, Huijiang; et al. (Frontiers in Genetics, 2021)
Cattle (Bos taurus), one is of the most widely distributed livestock in the world and provides us with high-quality milk and meat, which have a huge impact on the quality of human life. Therefore, accurate and complete transcriptome and genome annotation are of great value to the research of cattle breeding. In this study, we used error-corrected PacBio single-molecule real-time (SMRT) data to perform whole-transcriptome profiling in cattle. Then, 22.5 Gb of subreads was generated, including 381,423 circular consensus sequences (CCSs), among which 276,295 full-length non-chimeric (FLNC) sequences were identified. After correction by Illumina short reads, we obtained 22,353 error-corrected isoforms. A total of 305 alternative splicings events and 3795 alternative polyadenylation sites were detected by transcriptome structural analysis. Furthermore, we identified 457 novel genes, 120 putative transcription factors (TFs), and 569 novel long non-coding RNAs (lncRNAs). Taken together, this research improves our understanding and provides new insights into the complexity of full-length transcripts in cattle.